Building Resilient Value Chains After the Impact of the COVID-19 Disruption: Challenges for the Coffee Sector in Central America - Fromm, Ingrid (Frontiers in Sustainable Food Systems, 2022)
Coffee is an important agricultural sector in Central American, directly employing over 1.2 million people in Guatemala, Honduras, El Salvador, Nicaragua, and Costa Rica. Although export revenues from coffee trade have an overall positive effect on the gross domestic product (GDP) of these countries, poverty still prevails. The COVID-19 pandemic has placed additional pressure on the sector which is vulnerable to fluctuations in the international coffee prices, low productivity levels, and climate change effects and damages caused by pest and diseases. This paper examines the effects of the COVID-19 pandemic and analyzes if the sector is resilient to withstand unexpected external shocks such as the pandemic and the hurricanes which impacted the region in the last months of 2020. The capacity to absorb, adapt, and/or transform to these shocks was assessed from the perspective of small-scale coffee farmers, traders, exporters and the entire sector in two time periods—immediately after the start of the pandemic and after the coffee harvest. Although the actors in the coffee value chain absorbed these shocks and could withstand them, adaptation to the disruptions has been challenging for small-scale farmers. Despite the vulnerability to unexpected external shocks, results indicate that a long-term transformation of the sector to build resilience is likely to be slow.